Exercise as Medicine for Mental and Substance Use Disorders: A Meta-review of the Benefits for Neuropsychiatric and Cognitive Outcomes - Ashdown-Franks, Garcia; Firth, Joseph; Carney, Rebekah; Carvalho, Andre F.; Hallgren, Mats; Koyanagi, Ai; Rosenbaum, Simon; Schuch, Felipe B.; Smith, Lee; Solmi, Marco; Vancampfort, Davy; Stubbs, Brendon (Sports medicine (Auckland), 2020)
Background Exercise may improve neuropsychiatric and cognitive symptoms in people with mental disorders, but the totality of the evidence is unclear. We conducted a meta-review of exercise in (1) serious mental illness (schizophrenia spectrum, bipolar disorder and major depression (MDD)); (2) anxiety and stress disorders; (3) alcohol and substance use disorders; (4) eating disorders (anorexia nervosa bulimia nervosa, binge eating disorders, and (5) other mental disorders (including ADHD, pre/post-natal depression). Methods Systematic searches of major databases from inception until 1/10/2018 were undertaken to identify meta-analyses of randomised controlled trials (RCTs) of exercise in people with clinically diagnosed mental disorders. In the absence of available meta-analyses for a mental disorder, we identified systematic reviews of exercise interventions in people with elevated mental health symptoms that included non-RCTs. Meta-analysis quality was assessed with the AMSTAR/+. Results Overall, we identified 27 systematic reviews (including 16 meta-analyses representing 152 RCTs). Among those with MDD, we found consistent evidence (meta-analyses = 8) that exercise reduced depression in children, adults and older adults. Evidence also indicates that exercise was more effective than control conditions in reducing anxiety symptoms (meta-analyses = 3), and as an adjunctive treatment for reducing positive and negative symptoms of schizophrenia (meta-analyses = 2). Regarding neurocognitive effects, exercise improved global cognition in schizophrenia (meta-analyses = 1), children with ADHD (meta-analyses = 1), but not in MDD (meta-analyses = 1). Among those with elevated symptoms, positive mental health benefits were observed for exercise in people with pre/post-natal depression, anorexia nervosa/bulimia nervosa, binge eating disorder, post-traumatic stress disorder and alcohol use disorders/substance use disorders. Adverse events were sparsely reported. Conclusion Our panoramic meta-overview suggests that exercise can be an effective adjunctive treatment for improving symptoms across a broad range of mental disorders.